The Lung Cancer and Cigarette Smoking Web Page: A Pilot Study in Telehealth Promotion on the World Wide Web - Frederic W Grannis (Canadian Respiratory Journal)
BACKGROUND: Diseases caused by tobacco products are the number one preventable health problem.